Effects of diffusion and suction negative pressure on coalbed methane extraction and a new measure to increase the methane utilization rate. (1st June 2017) - Dong, Jun; Cheng, Yuanping; Jin, Kan; Zhang, Hao; Liu, Qingquan; Jiang, Jingyu; Hu, Biao
Highlights: The methane migration law in the process of underground CBM extraction is analyzed. The effects of diffusion and suction negative pressure on methane extraction are studied. A new measure to increase the methane concentration and utilization rate is proposed. Abstract: A constant suction negative pressure is used in coal mines owing to a lack of research on the effects of diffusion and suction negative pressure on methane extraction, resulting in the low methane concentration and utilization rate. In this study, Comsol Multiphysics is used to conduct a numerical solution of a gas–solid coupling model considering pseudo-steady diffusion in coal matrix, seepage in fractures, permeability evolution and coal deformation. The simulation results reveal the methane migration law and the effect of the diffusion process on the methane migration. The role and the influence degree of the suction negative pressure on methane extraction are studied, demonstrating that the suction negative pressure effect weakens gradually with the increasing methane extraction time. The methane concentrations of different suction negative pressures are calculated considering the changing effects of diffusion and suction negative pressure combined with the parallel relation between the methane migration and the air leakage, indicating that reducing the suction negative pressure can effectively increase the methane concentration. To change the present situation of the low methane concentration and utilization rate in coal mines, a new technical measure of methane extraction through parallel boreholes in groups is proposed to adjust the suction negative pressure and increase the methane utilization rate.